1991
DOI: 10.1203/00006450-199101000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin-6 by Fetal and Maternal Cells in Vivo during Intraamniotic Infection and in Vitro after Stimulation with Interleukin-1

Abstract: ABSTRACT. Amniotic fluid samples were obtained by transabdominal amniocentesis from 20 women in preterm labor (534 wk gestation). Concentrations of I M in culture-positive amniotic fluids (mean 8706 pg/mL, range 5100-14 446 pg/mL) were higher than those in culturenegative fluids (mean 1133 pg/mL, range 15-6534 pg/mL, p < 0.0001) or fluids from healthy term pregnancies (mean 196 pg/mL, range 55-790 pg/mL, p c 0.001). To assess possible sources of the IL-6 in amniotic fluid, we tested the ability of a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
7

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 9 publications
3
30
0
7
Order By: Relevance
“…For instance, using "light-density" blood cells, composed predominantly of lymphocytes and monocytes, we previously observed less IL-6 accumulation in supernatants of cells of preterm neonates than in cells of adults (34). Using whole blood cell cultures, Yachie et al (35) found no differences between term neonatal and adult cells in IL-6 accumulation after incubation with LPS derived from Escherichia coli.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, using "light-density" blood cells, composed predominantly of lymphocytes and monocytes, we previously observed less IL-6 accumulation in supernatants of cells of preterm neonates than in cells of adults (34). Using whole blood cell cultures, Yachie et al (35) found no differences between term neonatal and adult cells in IL-6 accumulation after incubation with LPS derived from Escherichia coli.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported conflicting findings concerning the responsiveness of LPS-stimulated neonatal monocytes. LPS-stimulated cord blood monocytes from term infants produced amounts of IL-6 similar to (41,51,74) or less than (47) those produced by adult monocytes. LPS-stimulated monocytes from preterm cord blood produced significantly less IL-6 (41, 51) than stimulated monocytes from term infants or adults.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, preterm neonates have significantly reduced proinflammatory cytokine (i.e. IL-1β, IL-6, TNF-α, figure 1) responses when stimulated with endotoxin (lipopolysaccharide, a potent TLR4 agonist) [24; 25; 26; 27; 28], IL-1 [29] or whole micro-organisms in vitro [30; 31; 32; 33]. They also produce limited amounts of antiviral interferon-α even though their proportion of blood plasmacytoid dendritic cells, main source of this cytokine, is comparable to term neonates or adults [34].…”
Section: Attenuated Toll-like Receptor Function In Preterm Neonatesmentioning
confidence: 99%